Identifying factors for pembrolizumab eligibility in head and neck cancer - Satoru Miyamaru; Daizo Murakami; Kohei Nishimoto; Yorihisa Orita (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Although immune checkpoint inhibitors (ICIs) are used as first-line treatments for recurrent or metastatic head and neck cancer (R/M HNC), there are many cases where the treatment is ineffective, making the assessment of efficacy crucial. In this study, we examined factors associated with the therapeutic effects of pembrolizumab. Methods We retrospectively analyzed 54 patients with R/M HNC treated with pembrolizumab from January 2020 to December 2022. We investigated the relationship between survival rates and various factors such as the combined positive score (CPS), histological subtypes, recurrent lesions, details of administered agents, sequence of administration, history of cetuximab use, and presence of immune-related adverse events (irAEs). Results The overall survival rates at 1-, 2, and 3 years were 57.4%, 41.8%, and 32.3%, respectively. The response and disease control rates were 31.5% and 51.9%, respectively. In the univariate analysis, a CPS of 20 or higher, first-line treatment, no history of cetuximab use, and the presence of irAEs was associated with better survival rates, whereas in the multivariate analysis, the first two factors were significantly associated with better survival. In this study, 16 of 20 cases had a CPS of 50 or higher, and 7 had a CPS of 90 or higher, indicating that a large number of high CPS cases were included, which is believed to have contributed to the results of this study. Conclusion In patients with a CPS of 20 or higher, pembrolizumab can be administered as first-line treatment, with favorable expected therapeutic effects.